Influence of Row Spacing on Root Yield and Yield Components of Fodder Beet Beta vulgaris var. crassa Mansf. in the Black Sea Coastal Region - Necdet Çamaş; Sabahattin Albayrak (Journal of Agricultural Sciences)
Effects of four row spacing 30, 40, 50 and 60 cm on root yield and some yield components of fodder beet Beta vulgaris var. crassa Mansf. cultivar Ecdorot and cultivar Ecdogelb were evaluated in Çarşamba and Bafra plains, Turkey in the 2002 and 2003 growing seasons. The root yield, root dry matter rate, root dry matter yield, root diameter, root length, and sugar content were determined. Row spacing significantly affected most of the yield components determined in both locations. Root yield, root dry matter yield, root diameter, and root length increased along with increased of row spacing. However, root dry matter rate and sugar content were not greatly influenced by row spacing. The highest root dry matter was obtained from 50-60 cm row spacing for both cultivars and locations. Cultivar Ecdorat had higher yield data and this cultivar was also found more stable than cultivar Ecdogelb in the Black Sea costal region of Turkey